Accumulation of dry matter, nitrogen, phosphorus, and potassium in cassava (Manihot esculenta Crantz) - Oelsligle, D.D. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
In ynca (Manihot esculenta Crantz cv. 'Guaxupe 454') the accumulation of dry matter, nitrogen, phosphorus and potassium during the period of rapid growth were quite similar. The concentration of the three nutrients in the upper part and the tillers decreased with time. A tiller yield of 43 ton/ha removed 174, 21 and 125 g/ha of N, P and K, respectively.